Comparative assessmenr in differenr condirions of a program for rhe learning of reading and writing - Bazán Ramírez, Aldo (1997)
Dara collected under differenr didacric condirions and evaluarion steps of a program for the learning of reading and wriring are reponed. The firsr didacric condirion corresponds ro an inirial phase of projecrion ro rhe communiry wirh rhe reachers help (Mares, Plancarre y Rueda, 1994). The second evaluarion is about a tesr applied in four experimemal programs designed by Mares et. al. based en rhe behavioral taxonomy developed by Ribes and Lopez (1985). Finally, rhe rhird condition corresponds ro rhe adaptarion of a reading and writing program for 40 children (Mares, Bazan and Farfan, 1995). In all cases, rhe effecriveness of rhe program was measured based en rhe mechanical and funcrional aspecrs of rhe wrirren language, and a comparison wirh other programs used by a differem group of reachers was established.